ПРОФЕСІЙНИЙ РОЗВИТОК ПЕДАГОГІЧНИХ ПРАЦІВНИКІВ ЗАКЛАДІВ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ (Innovative professional education, 2022)
The educational and professional program of professional development is a system of educational components of the professional developmentof scientific and pedagogical workers of institutions of vocational pre-highereducation. The educational and professional program of professional development is aregulatory document for the organization of the educational process for various categories of students at the University of Education Management
Keywords: professional development; teaching staf; educational and professional program; educational process